Composite current collector with high bonding strength
By adjusting the metal layer parameters and setting the base layer in the composite fluid, the problem of metal layer peeling is solved, the adhesion and battery energy density are improved, and higher binding force and lighter composite fluid are achieved.
Patent Information
- Application Number
- CN202411202304.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
AI Technical Summary
The metal layer in the composite fluid collecting fluid is prone to fall off the support layer. The existing solutions increase the weight of the composite fluid collecting fluid and reduce the energy density of the battery.
By adjusting the average particle size and surface density of the metal layer particles in the composite fluid, it is within the range of 0.1≥K/X≥0.05, the bonding force between the metal layer and the support layer is increased, and a base layer is provided on the support layer to improve the Adhesive strength to avoid unnecessary structural increase.
Without increasing the weight of the composite collector, the adhesion between the metal layer and the support layer is improved, the risk of shedding is reduced, and the energy density and service life of the battery are improved.
Smart Images

Figure CN119252925A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite current collectors, in particular to a composite current collector with high bonding strength. Background Art
[0002] With the development of science and technology, composite current collectors have gradually attracted attention as a new generation of current collector materials. Composite current collectors have a sandwich structure, with a polymer layer in the middle and metal films on the top and bottom, and have better safety performance and energy density.
[0003] The main problem currently faced by the composite current collector is that the metal layer is easy to fall off from the supporting layer. There are many solutions to this problem, such as the patent with publication number CN118136852A. This patent uses magnetron sputtering after introducing conductive carbon into the polymer substrate. Compared with the bonding force between polymer and copper, the bonding force between C / polymer and copper is stronger, so the bonding between the plated copper layer and the substrate is more firmly. For example, the patent with publication number CN221176268U fixes the position between the layers in the current collector body through a locking mechanism, effectively avoiding the peeling between the layers after the current collector is used for a long time. The above methods all achieve the problem of preventing the metal layer from falling off the supporting layer by setting various structures and materials on the current collector, but these methods all increase the weight on the current collector itself, which increases the weight of the composite current collector and reduces the energy density of the battery.
[0004] Therefore the prior art still needs to be improved and enhanced. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a composite current collector with high bonding strength.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The present invention provides a composite current collector with high bonding strength, comprising a support layer and a metal layer, wherein the metal layer is arranged on the surface of the support layer, the average particle size of the metal layer particles is X, the surface density of the metal layer is K, wherein 0.1≥K / X≥0.05.
[0008] Furthermore, in the composite current collector with high bonding strength, the average particle size X of the metal layer is 30nm-60nm, and the surface density K of the metal layer satisfies 2.1g / m 2 -3g / m 2 .
[0009] Furthermore, for the composite current collector with high bonding strength, a primer layer is provided between the support layer and the metal layer.
[0010] Furthermore, in the composite current collector with high bonding strength, the primer layer is a metal coating or a non-metallic layer.
[0011] Furthermore, in the composite current collector with high bonding strength, the surface density of the primer layer is greater than the surface density of the metal layer.
[0012] Furthermore, in the composite current collector with high bonding strength, when the base layer is a non-metallic layer, the ratio of the surface density of the base layer to its particle size is smaller than the ratio of the surface density of the metal layer to its particle size.
[0013] Furthermore, in the composite current collector with high bonding strength, the upper and lower surfaces of the support layer are both provided with metal layers, and the ratio of the surface density of the metal layer on the upper surface of the support layer to its particle size is smaller than the ratio of the surface density of the metal layer on the lower surface of the support layer to its particle size.
[0014] Furthermore, for the composite current collector with high bonding strength, the ratio of the surface density of the primer layer on the upper surface of the support layer to its particle size is smaller than the ratio of the surface density of the primer layer on the lower surface of the support layer to its particle size.
[0015] Furthermore, in the composite current collector with high bonding strength, the thickness of the support layer is 3um-8um, the thickness of the primer layer is 30-100nm, and the thickness of the metal layer is 900-1000nm. The mass of the primer layer is less than the mass of the support layer, and the mass of the metal layer is less than the mass of the support layer.
[0016] Furthermore, in the composite current collector with high bonding strength, the supporting layer is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin; when the metal layer is an aluminum layer, the primer layer is an aluminum oxide layer; when the metal layer is a copper layer, the primer layer is a nickel-copper alloy layer.
[0017] Compared with the prior art, the present invention provides a composite current collector with high bonding strength, including a support layer and a metal layer, wherein the metal layer is arranged on the surface of the support layer, the average particle size of the metal layer is X, and the surface density of the metal layer is K, wherein 0.1≥K / X≥0.05. The present invention mainly changes the bonding force between the metal layer and the support layer of the composite current collector by changing the parameter properties of the composite current collector, thereby avoiding setting other unnecessary structures on the support layer to affect the weight of the composite current collector. The metal layer in the composite current collector of the present invention within the range of 0.1≥K / X≥0.05 has a higher bonding force and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0019] Figure 1 This is a schematic diagram of the structure of a composite current collector with high bonding strength provided by the present invention.
[0020] Description of Figure Numbers:
[0021] Support layer 100
[0022] Base layer 200
[0023] Metal layer 300 DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0026] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0027] like Figure 1 As shown, the present invention provides a composite current collector with high bonding strength, including a support layer 100 and a metal layer 300, wherein the metal layer 300 is arranged on the surface of the support layer 100, the average particle size of the metal layer 300 is X, and the surface density of the metal layer 300 is K, wherein 0.1≥K / X≥0.05. The present invention mainly changes the bonding force between the metal layer 300 of the composite current collector and the support layer 100 by changing the parameter properties of the composite current collector, thereby avoiding setting other unnecessary structures on the support layer 100 to affect the weight of the composite current collector. The metal layer 300 in the composite current collector of the present invention within the range of 0.1>K / X>0.05 or 0.1≥K / X≥0.05 has a higher bonding force and is not easy to fall off. After many experiments, the inventor found that the metal layer 300 within this range has a higher bonding force and is not easy to fall off. The specific principle is not yet clear. The inventor estimates that this is because the particle size of the metal layer 300 is within this range under this surface density condition, especially within this ratio range, the contact area between particles is the largest, and the bonding force with the support layer 100 and the microscopic bonding force between particles are stronger.
[0028] Furthermore, in the composite current collector with high bonding strength provided by the present invention, the average particle size X of the metal layer 300 can be 30nm-60nm, and the surface density K of the metal layer 300 satisfies 2.1g / m 2 -3g / m 2 .
[0029] Preferably, the mass of the metal layer 300 is less than the mass of the support layer 100, so that the total mass of the composite current collector can be smaller, so that the electrical device using the product of the present invention, such as a lithium battery, can be lighter and have a higher energy density. Preferably, the mass of the base layer 200 is less than the mass of the support layer 100, which is conducive to further reducing the total mass of the composite current collector. The low-quality base layer 200 can also reduce the formation of holes in the support layer 100 by the base layer 200, and can also reduce the cost of the composite current collector of the present application, because the base layer 200 of the present application requires less amount and the production process consumes less energy.
[0030] Furthermore, in the composite current collector with high bonding strength provided by the present invention, a primer layer 200 is provided between the support layer 100 and the metal layer 300. Furthermore, in the composite current collector with high bonding strength provided by the present invention, the primer layer 200 is a metal coating or a non-metal layer 300.
[0031] Furthermore, in the composite current collector with high bonding strength provided by the present invention, the surface density of the primer layer 200 is greater than the surface density of the metal layer 300. This can prevent the components in the electrolyte from penetrating into the support layer 100. When a general composite current collector is used in a battery, the components in the electrolyte penetrate into the support layer 100, and the electrolyte contacts the support layer 100 to corrode the support layer 100, which easily reduces the life of the composite current collector.
[0032] Furthermore, in the composite current collector with high bonding strength provided by the present invention, when the base layer 200 is a non-metal layer, the ratio of the surface density of the base layer 200 to its particle size is smaller than the ratio of the surface density of the metal layer 300 to its particle size. This is conducive to the heat extraction of the composite current collector, and at the same time, the base layer 200 and the metal layer 300 are in closer contact, which increases the bonding force between the metal layer 300 and the base layer 200, and also increases the bonding force between the base layer 200 and the support layer 100.
[0033] Furthermore, in the composite current collector with high bonding strength provided by the present invention, the upper and lower surfaces of the support layer 100 are both provided with a metal layer 300, and the ratio of the surface density of the metal layer 300 on the upper surface of the support layer 100 to its particle size is less than the ratio of the surface density of the metal layer 300 on the lower surface of the support layer 100 to its particle size. In this way, the present invention can increase the heat conduction of the composite current collector while satisfying the bonding force, that is, it is convenient to guide the temperature from one side of the composite current collector to the other side. Further, in the composite current collector with high bonding strength provided by the present invention, the ratio of the surface density of the base layer 200 on the upper surface of the support layer 100 to its particle size is less than the ratio of the surface density of the base layer 200 on the lower surface of the support layer 100 to its particle size. This is conducive to further increasing the heat conduction of the composite current collector while satisfying the bonding force, that is, it is convenient to guide the temperature from one side of the composite current collector to the other side.
[0034] Furthermore, in the composite current collector with high bonding strength provided by the present invention, the thickness of the support layer 100 is 3um-8um. The thickness of the support layer 100 is relatively low, which can reduce the mass of the composite current collector. The support layer 100 is made of non-conductive material, which greatly improves the safety performance compared to pure metal current collectors. The thickness of the base layer 200 is 30-100nm, and the thickness of the metal layer 300 is 900-1000nm. The metal layer 300 at this thickness can make the composite current collector meet the requirements of the flow capacity, and the base layer 200 at this thickness can also help reduce the weight.
[0035] Further, in the composite current collector with high bonding strength provided by the present invention, the support layer 100 is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene oxide, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin. The support layer 100 of the present invention can be a film made of any non-conductive material.
[0036] The composite current collector of the present invention can be prepared by various methods. First, a section of the support layer 100 (film) is taken, and then a desired coating thickness is formed on the support layer 100 by various methods.
[0037] Specifically, in the first method provided by the present invention, a vacuum coating method is directly used to form a base layer 200 and a metal layer 300 on the support layer 100. Here and in the following example, the metal layer 300 is copper. The copper is formed on the support layer 100 mainly by magnetron sputtering, that is, the support layer 100 is placed in a magnetron sputtering machine and coated in a vacuum magnetron sputtering device. Through the PVD (Physical vapor deposition) method, the vacuum of the equipment body and the process vacuum are controlled at certain parameters, and pure argon gas is introduced. Under vacuum conditions, electrons collide with argon atoms during the leap process, ionizing them to produce Ar positive ions and new electrons; constrained by the magnetic field on the back of the magnetron sputtering target, most electrons are confined around the magnetic field, and Ar ions are accelerated to fly toward the cathode target under the action of the electric field, and bombard the surface of the Cu alloy target (the present application uses a nickel-copper alloy target) with high energy, causing the target material to sputter. Among the sputtered particles, neutral target atoms or part of the ions are deposited on the base film to form a base layer 200, and then continue to use this method to sputter copper on the base layer 200 multiple times in the magnetron sputtering machine, so that the base layer 200 has a thickness of 30-100nm and the metal layer 300 is 900-1000nm. Of course, in the above method, the vacuum evaporation method can also be used to form the metal layer 300 (that is, the copper layer). The metal layer 300 is formed on the base layer 200.
[0038] Specifically, in the second method provided by the present invention, magnetron sputtering is first used to form the base layer 200, and then vacuum evaporation is performed, and finally the metal layer 300 is formed on the support layer 100 by water electroplating. Magnetron sputtering refers to: coating in a vacuum magnetron sputtering device. Through the PVD (Physical vapor deposition) method, the vacuum of the equipment body and the process vacuum are controlled at certain parameters, and pure argon gas is introduced. Under vacuum conditions, electrons collide with argon atoms during the leap process, causing them to ionize and produce Ar positive ions and new electrons; constrained by the magnetic field on the back of the magnetron sputtering target, most of the electrons are constrained around the magnetic field, and the Ar ions are accelerated to fly toward the cathode target under the action of the electric field, and bombard the surface of the Cu alloy target with high energy, causing the target material to sputter. Among the sputtered particles, neutral target atoms or part of the ions are deposited on the base film to form a thin film, which is a 30nm-100nm base layer 200 formed in this application. Electroplating means: using phosphor copper balls as anodes, placing the phosphor copper balls in anode bags made of titanium blue, and then immersing the entire anode bag in acidic reagents (acidic sulfuric acid solution: sulfuric acid 90-170g / L, copper ions 50-160g / L, chloride ions 30-60ppm), with the metal layer 300 on the membrane surface as the cathode, the membrane surface passes through the rollers under the reagent tank, and the membrane surface is immersed in the reagent for ion migration replacement. After the membrane surface obtains electrons, a copper layer will be formed. The thickness of the copper accumulation layer is 900nm, and the speed of the membrane passing is 3-5m / min. Evaporation means: a physical phase deposition (PVD) method that melts the metal into a liquid state, forms metal vapor and begins to volatilize, and then condenses the copper atoms in the vapor and deposits and grows on the surface of the polymer material. The vacuum evaporation step is added after magnetron sputtering to increase the deposition rate. The deposition rate of vacuum evaporation is 3-4 times that of magnetron sputtering, which can quickly replenish the copper film to a thickness suitable for electroplating.
[0039] When the metal layer 300 of the present invention is an aluminum layer, the base layer 200 is preferably an aluminum oxide layer. At the same time, the production method preferably first uses a vacuum evaporation method to form a base layer 200 aluminum oxide on the support layer 100, and then uses a vacuum evaporation method to form a metal aluminum layer on the base layer 200. Such a production method can greatly reduce the complexity of the process and reduce the oxidation of aluminum metal during the production process. Among them, when producing aluminum oxide, the evaporation source uses an evaporation boat to evaporate, which can improve the production efficiency and reduce the possibility of the support layer 100 being burned through by high-temperature particles. In the process of forming aluminum metal, a crucible should be used to improve efficiency, because the thickness of aluminum is thicker than that of aluminum oxide. Using a crucible can form a large number of aluminum layers at one time, thereby improving production efficiency.
[0040] When the metal layer 300 of the present invention is copper, the base layer 200 is preferably a nickel-copper alloy, which can improve the bonding force between the metal layer 300 and the base layer 200. At this time, the metal layer 300 and the base layer 200 can be formed by magnetron sputtering.
[0041] The present invention also provides corresponding experimental data, including embodiments and comparative examples. The supporting layers of the embodiments and comparative examples are both made of PP film, and the material of the metal layer is copper. The average particle size of the metal layer in embodiment 1 is 30 nm, and the surface density of the metal layer is 3 g / m 2 , at this time, the value of K / X is 0.1; the average particle size of the metal layer in Example 2 is 60nm, and the surface density of the metal layer is 3g / m 2 , at this time, the value of K / X is 0.05. The average particle size of the metal layer of comparative example 1 is 60nm, and the surface density of the metal layer is 2.1g / m 2 , at this time, the value of K / X is 0.035; the average particle size of the metal layer of comparative example 2 is 30nm, and the surface density of the metal layer is 3.5g / m 2 , at this time, the value of K / X is 0.12; the bonding strength test of the metal layer and the support layer adopts the adhesive method, which is: at room temperature and pressure, use 3M double-sided tape to evenly stick it on the stainless steel plate, and then evenly stick the sample to be tested on the double-sided tape with a width of 2cm. Use a high-speed rail tensile machine to peel off the conductive layer and the insulating layer of the sample to be tested. According to the data graph of tension and displacement, read the maximum tension, divide the read value by 20 (unit N), and calculate the bonding strength between the metal layer and the support layer, that is, the bonding strength F (N / mm) between the substrate layer and the conductive layer in the composite current collector. The following is the experimental data:
[0042] Binding force F(N / mm) Example 1 0.45 Example 2 0.47 Comparative Example 1 0.35 Comparative Example 2 0.31
[0043] It can be seen that the composite current collector of the present invention has a higher binding force.
[0044] In summary, the present invention provides a composite current collector with high bonding strength, including a support layer and a metal layer, wherein the metal layer is arranged on the surface of the support layer, the average particle size of the metal layer is X, and the surface density of the metal layer is K, wherein 0.1≥K / X≥0.05. The present invention mainly changes the bonding force between the metal layer of the composite current collector and the support layer by changing the parameter properties of the composite current collector, thereby avoiding setting other unnecessary structures on the support layer to affect the weight of the composite current collector. The metal layer in the composite current collector of the present invention within the range of 0.1≥K / X≥0.05 has a higher bonding force and is not easy to fall off. After unlimited experiments, the inventor found that the metal layer within this range has a higher bonding force and is not easy to fall off. The specific principle has not yet been clarified. The inventor estimates that it is because the metal layer has a particle size within this range, especially within this ratio range, and the contact area between particles is the largest under this surface density condition, and the bonding force with the support layer and the microscopic bonding force between particles are stronger.
[0045] Moreover, in the composite current collector with high bonding strength provided by the present invention, the surface density of the base layer is greater than the surface density of the metal layer. This can prevent the components in the electrolyte from penetrating into the support layer. When a general composite current collector is used in a battery, the components in the electrolyte penetrate into the support layer, and the electrolyte contacts the support layer and corrodes the support layer, which easily reduces the life of the composite current collector. Furthermore, in the composite current collector with high bonding strength provided by the present invention, when the base layer is a non-metallic layer, the ratio of the surface density of the base layer to its particle size is less than the ratio of the surface density of the metal layer to its particle size. This is conducive to the extraction of heat from the composite current collector, while making the contact between the base layer and the metal layer closer, increasing the bonding force between the metal layer and the base layer, and also increasing the bonding force between the base layer and the support layer.
[0046] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A composite current collector with high bonding strength, characterized in that: It comprises a support layer and a metal layer, wherein the metal layer is arranged on the surface of the support layer, the average particle size of the particles of the metal layer is X, the surface density of the metal layer is K, wherein 0.1≥K / X≥0.
05.
2. The composite current collector with high bonding strength according to claim 1, characterized in that: The average particle size X of the metal layer is 30nm-60nm, and the surface density K of the metal layer satisfies 2.1g / m 2 -3g / m 2 .
3. The composite current collector with high bonding strength according to claim 2, characterized in that: A primer layer is arranged between the support layer and the metal layer.
4. The composite current collector with high bonding strength according to claim 3, characterized in that: The primer layer is a metal coating or a non-metal layer.
5. The composite current collector with high bonding strength according to claim 4, characterized in that: The surface density of the primer layer is greater than the surface density of the metal layer.
6. The composite current collector with high bonding strength according to claim 4, characterized in that: When the base layer is a non-metal layer, the ratio of the surface density of the base layer to its particle size is smaller than the ratio of the surface density of the metal layer to its particle size.
7. The composite current collector with high bonding strength according to claim 1, characterized in that: The upper and lower surfaces of the support layer are both provided with metal layers, and the ratio of the surface density of the metal layer on the upper surface of the support layer to its particle size is smaller than the ratio of the surface density of the metal layer on the lower surface of the support layer to its particle size.
8. The composite current collector with high bonding strength according to claim 4, characterized in that: The ratio of the surface density of the primer layer on the upper surface of the support layer to its particle size is smaller than the ratio of the surface density of the primer layer on the lower surface of the support layer to its particle size.
9. The composite current collector with high bonding strength according to claim 3, characterized in that: The mass of the metal layer is smaller than that of the supporting layer, the mass of the primer layer is smaller than that of the supporting layer, the thickness of the supporting layer is 3um-8um, the thickness of the primer layer is 30-100nm, and the thickness of the metal layer is 900-1000nm.
10. The composite current collector with high bonding strength according to any one of claims 1 to 9, characterized in that: The support layer is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin; when the metal layer is an aluminum layer, the primer layer is an aluminum oxide layer; when the metal layer is a copper layer, the primer layer is a nickel-copper alloy layer.
